Corporate Ethics and Sustainable Governance in ASEAN: The Role of ESG Practices in Enhancing Long-Term Competitiveness - Virginia Grace Yvonne Waruwu; Marisa Meilano Rizki (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the critical relationship between corporate ethics, Environmental, Social, and Governance (ESG) practices, and sustainable competitiveness among ASEAN corporations. As regional economies transition toward responsible capitalism, ethical governance has emerged as a strategic determinant of long-term value creation. Using a qualitative-comparative approach supported by secondary data, the research analyzes regulatory developments, ESG disclosure performance, and governance maturity across six ASEAN countries. The findings reveal that firms with strong ethical foundations and integrated ESG frameworks achieve higher investor confidence, enhanced transparency, and superior market resilience. Singapore and Malaysia lead in governance and ESG adoption, while emerging markets like Indonesia, Vietnam, and the Philippines demonstrate rapid institutional progress. The study highlights that ethical consistency and ESG integration function as dual catalysts for reducing operational risks, improving innovation capacity, and fostering social legitimacy. ASEAN’s movement toward harmonized sustainability governance signifies a structural realignment of corporate identity, positioning ethics and ESG as central pillars of sustainable regional competitiveness